Welcomeness for people with substance use disorders to general practice: a qualitative study. (18th November 2021) - Abbott, Penelope; Watt, Kelly; Magin, Parker; Davison, Joyce; Hu, Wendy C Y
Abstract: Background: Good primary care for people with substance use disorders (SUDs) is crucial given the high prevalence of SUDs and overdose deaths. Objective: To explore general practice care for people with a history of SUDs from the perspectives of women involved with the criminal justice system. Methods: Qualitative interview study with pre- and postrelease interviews, undertaken in Australian prisons and community settings. We utilized thematic analysis informed by constructivist grounded theory. Results: We undertook 65 interviews with 39 women. Access to and experience of general practitioner (GP) care was affected by perceived welcomeness, decisions around disclosure, and consultation experiences related to medication prescription. Participants reported that they were not as welcome as other patients, welcome could be conditional on not disclosing SUDs or only requesting unrelated healthcare, and GPs did not always differentiate between past and current drug use. Participants perceived difficulty finding general practices where the potential benefit of disclosing SUDs outweighed the risks of stigmatized reactions and lack of GP skills and interest. Participants did not always recognize that care beyond physical health could occur in general practice. The pejorative implications of labelling patients as "doctor shoppers" were challenged by participants, as they considered it could be necessary to attend multiple GPs to find a welcoming practice. Conclusions: People with histories of SUDs do not uniformly experience welcomeness in general practice, perpetuating poor engagement in healthcare and poor outcomes related to SUDs. Programmes targeting prescription drug misuse through general practice should also promote welcomeness for people with SUDs.